2010
DOI: 10.1158/1078-0432.ccr-09-0260
|View full text |Cite
|
Sign up to set email alerts
|

Mining Tissue Microarray Data to Uncover Combinations of Biomarker Expression Patterns that Improve Intermediate Staging and Grading of Clear Cell Renal Cell Cancer

Abstract: Purpose: Tumor stage and nuclear grade are the most important prognostic parameters of clear cell renal cell carcinoma (ccRCC). The progression risk of ccRCC remains difficult to predict particularly for tumors with organ-confined stage and intermediate differentiation grade. Elucidating molecular pathways deregulated in ccRCC may point to novel prognostic parameters that facilitate planning of therapeutic approaches.Experimental Design: Using tissue microarrays, expression patterns of 15 different proteins we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 46 publications
2
72
0
2
Order By: Relevance
“…Cyclin D1 is a cell-cycle regulator crucial for the G 1 -S transition (35) and is overexpressed in many cancers including colorectal and breast carcinoma (36,37). We found that cyclin D1 was overexpressed in 43% of the primary ccRCC samples, a finding that was similar to the previous published data (38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cyclin D1 is a cell-cycle regulator crucial for the G 1 -S transition (35) and is overexpressed in many cancers including colorectal and breast carcinoma (36,37). We found that cyclin D1 was overexpressed in 43% of the primary ccRCC samples, a finding that was similar to the previous published data (38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
“…There is no association identified between Cyclin D1 expression and ccRCC prognosis (40), although Cyclin D1 overexpression is associated with shorter patient survival in other cancers and thus represents an interesting therapeutic target (44). However, cyclin D1 is difficult to target as it is expressed in the cytosol and lacks intrinsic enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two modern approaches within the scope of computational pathology try to solve this question from a frequentist [89] and a Bayesian [87] point of view.…”
Section: Higher Order Interactionsmentioning
confidence: 99%
“…The control group consisted of 40 pT1 and pT2 clear cell renal cell carcinomas with low Fuhrman differentiation grade (1 and 2) from a recently published study. 4 …”
Section: Tumor Specimensmentioning
confidence: 99%
“…3 Recently, we comprehensively analyzed pVHL-and phosphatase and tensin homolog (PTEN)-controlled pathways in 4800 clear cell renal cell carcinoma patients. 4 It was shown that the expression status of p27, PTEN, carbonic anhydrase 9 (CAIX) and phosphorylated ribosomal protein S6 is crucial for the biological behavior of sporadic clear cell renal cell carcinoma.…”
mentioning
confidence: 99%